Legal Protection For Auction Winner Execution Of Liability Rights Auction No. 49 / Pdt.G / 2011 / Pn.Pkl (A case study in Kospin, Pekalongan) - Ely Cahyawati; Lathifah Hanim (Jurnal Akta, 2018)
The research objective was to examine the legal protection against the winner of the auction the object is blocked by the land office to analyze the reason for blocking, and the responsibility of the winning bidder auction officials that the object is blocked by the land office How Legal protection for the Auction Winner of the auction Exsekusi security rights. The method used is as an additive normative juridical research interviews to the land office and Legal Section Kospin pekalongan Services. Based on the results of the study concluded eat: first, Consideration of the Land Office to block the process of reverse auction execution object name Encumbrance (Civil Case Study No.25 / Pdt.G / 2011 / PN.Tegal) is: Based on Government Regulation No. 24 of 1997 Article 45, which reads the Head of the Land Office reserves the right to delay on behind the object name that is being problematic of land ", as well as the attitude of prudence to avoid the risk in the future in order not to become a defendant in the case; Secondly, legal protection for the winner of the auction execution Encumbrance Land Office blocked the auction of objects is very weak, as in this case the winning bidder can not do anything but just wait until the court decision is completed; Third, auction Officials Responsibility for the blocking of the auction objects at the office of the Land does not exist at all.Keywords: Legal Protection, Winning Bidder, Execution Mortgage.